Impulse Buying: The Influence of Customer Behavior with User Experience Moderation - Kadek Bagus Candra Diputra; I Gede Sanica (Quantitative Economics and Management Studies, 2023)
The current study aimed to investigate the role of visual merchandising strategies, consumer trust in online stores, and shopping lifestyles that can increase impulsive purchases on the Shopee e-commerce. Furthermore, this study also investigates the role of user experience as a moderating construct. Current study was conducted at Denpasar City. This study targets the entire population who use the Shopee e-commerce platform in Denpasar City. Through purposive sampling and the Roscoe formula, 125 respondents were obtained. Empirical data was collected through questionnaires and analyzed using the PLS-SEM approach. The study findings confirm that a crucial component in creating impulsive buying actions among consumers is a lifestyle that always wants to increase value and self-image. Moreover, a good user experience also becomes the driving factor that creates unplanned purchases, especially when various promotions are held. Interesting findings in this study are that there is no significant relationship between visual merchandising and online store belief constructs on impulse buying and the failure of user experience in moderating the relationship between each construct. These findings demonstrate that consumers' impulsive buying activities are not based on trust or the appearance of a visual presentation of the product.